Philanthropy and Social Research: A Rather Neglected Part of Social Science History - Balon, Jan (Teorie vědy / Theory of Science, 2013)
This study reviews the book: Christian FLECK, A Transatlantic History of the Social Sciences: Robber Barons, the Third Reich and the Invention of Empirical Social Research. London: Bloomsbury Academic 2011. It concentrates mainly on one part of Fleck's account: on the analysis of the ways foundations and philanthropic organizations profiled and shaped the research agenda and the politics of knowledge in the social sciences. It is demonstrated how the definition of science promoted in the 1920's by major American philanthropic foundations fundamentally changed the very idea of research and produced many institutional innovations. The relation of philanthropyand social scientific research is pursued both in a general sense, in terms of formative ideas influencing the development of social sciences and the actual scientific practice, and in relation to various national research graditions, the role of individual foundations and the activities of foundations aiming to promote their conception of scientific research. A special attention is paid to the Rockefeller Foundation, as its concept of "realistic" research significantly influenced the institutional history of the social sciences. This study also focuses on the style of writing, which is employed in contemporary texts on the history of foundations, especially in comparison with the still prevailing accent on the study of social science's intellectual history.